Covering active material, electrode material, battery, and method for manufacturing battery

By covering the fluoride solid electrolyte layer on the surface of the active substance of the battery and dispersing it in the organic dispersion medium, a fine structure is formed, and the problem of increasing battery resistance is solved, better interface contact and protection effect is achieved, and the durability of the battery is improved and charge and discharge efficiency.

CN119318032APending Publication Date: 2025-01-14PANASONIC HOLDINGS CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044687.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-05-09
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The problem of the increase in resistance of existing batteries in the durability test is mainly due to the increase in resistance caused by the oxidation and decomposition of solid electrolytes, and the high peeling rate of the cover layer leads to insufficient protection effect.

Method used

The cover active substance is used, and its surface is covered with a solid electrolyte layer with fluoride, with a peeling rate of less than 42%, and is dispersed in an organic dispersion medium to form a fine particle-like structure and a porous structure to improve the interface contact effect.

Benefits of technology

It effectively suppresses the increase in battery resistance, improves the durability and charging and discharging efficiency of the battery, reduces the resistance, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318032A_ABST
    Figure CN119318032A_ABST
Patent Text Reader

Abstract

This coated active material (130) is provided with an active material (110) and a coating layer (111) that contains a first solid electrolyte and covers at least a part of the surface of the active material (110), the first solid electrolyte containing a fluoride, and the coating layer (111) containing a second solid electrolyte containing a fluoride. The mass of the coating layer (111) that is peeled off from the active material (110) when the coating active material (130) is dispersed in the organic dispersion medium is less than 42% of the total mass of the coating layer (111).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a covering active material, an electrode material, a battery, and a method for manufacturing the battery. Background Art

[0002] Non-Patent Document 1 discloses a battery using a sulfide as a solid electrolyte.

[0003] Prior art literature

[0004] Non-patent literature

[0005] Non-patent document 1: Journal of Power Sources 159 (2006), p193-199. Summary of the invention

[0006] Problems to be solved by the invention

[0007] In the conventional technology, it is required to suppress the increase in battery resistance caused by a durability test.

[0008] Means for solving problems

[0009] The present disclosure provides a covering active material, wherein the covering active material comprises:

[0010] Active substances, and

[0011] a covering layer comprising a first solid electrolyte and covering at least a portion of the surface of the active material;

[0012] The first solid electrolyte contains fluoride,

[0013] When the coated active material is dispersed in an organic dispersion medium, the mass of the coating layer that is peeled off from the active material is less than 42% of the total mass of the coating layer.

[0014] Effects of the Invention

[0015] According to the present disclosure, it is possible to suppress an increase in resistance of a battery caused by a durability test. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a cross-sectional view showing a schematic structure of a covering active material in the first embodiment.

[0017] Figure 2 It is a cross-sectional view showing a schematic structure of a covering active material in a modified example.

[0018] Figure 3 This is a cross-sectional view schematically showing the structure of an electrode material in the second embodiment.

[0019] Figure 4 This is a cross-sectional view schematically showing the structure of a battery in the third embodiment.

[0020] Figure 5 This is a flow chart showing a method for manufacturing a battery.

[0021] Figure 6 This is a graph showing the relationship between DC resistance and peeling rate.

[0022] Figure 7 This is a graph showing the relationship between the increase rate of resistance and the peeling rate.

[0023] Figure 8 This is a SEM image of the coated active material of Example 3. DETAILED DESCRIPTION

[0024] (Knowledge that forms the basis of this disclosure)

[0025] For example, when the active material is in contact with the solid electrolyte, the solid electrolyte may be oxidatively decomposed during the battery charging. This tendency is significant when the solid electrolyte is a sulfide solid electrolyte with poor oxidation resistance. In order to solve this problem, the surface of the active material is covered with a covering material with excellent oxidation resistance such as a halide solid electrolyte.

[0026] Here, the present inventors noticed that even if the composition of the covering material is the same, the battery characteristics, especially the resistance, will be different. Furthermore, the present inventors found that there is a correlation between the amount of the covering material peeled off from the active material and the battery characteristics, and thus came up with the present disclosure.

[0027] (Overview of one aspect of the present disclosure)

[0028] The coated active material according to the first aspect of the present disclosure is a coated active material comprising an active material and a coating layer.

[0029] The covering layer includes a first solid electrolyte and covers at least a portion of the surface of the active material.

[0030] The first solid electrolyte contains fluoride,

[0031] When the coated active material is dispersed in an organic dispersion medium, the mass of the coating layer that is peeled off from the active material is less than 42% of the total mass of the coating layer.

[0032] According to the present disclosure, it is possible to suppress an increase in resistance of a battery caused by a durability test.

[0033] In the second aspect of the present disclosure, for example, according to the covering active material of the first aspect, the absorbance at a wavelength of 400 nm obtained by measuring the supernatant obtained by dispersing and precipitating the above-mentioned covering active material in the above-mentioned organic dispersion medium may also be less than 0.63. With such a configuration, the characteristics of the battery can be further improved.

[0034] In the third aspect of the present disclosure, for example, according to the covering active material of the first or second aspect, the above-mentioned covering layer may also have a particulate-like structure including a plurality of particles with a diameter of 500 nm or less. If the covering layer has a fine particulate-like structure, the deformation of the covering layer can be promoted during the manufacture of the electrode plate, and thus a good interface can be formed between the covering active material and other materials. As a result, the resistance of the battery can be further reduced.

[0035] In the fourth aspect of the present disclosure, for example, according to the covering active material of any one of the first to third aspects, the above-mentioned covering layer may also have a plurality of pores with a diameter of 50 nm or less. If the covering layer has fine pores, the deformation of the covering layer can be promoted during the manufacture of the electrode plate, and thus a good interface can be formed between the covering active material and other materials. As a result, the resistance of the battery can be further reduced.

[0036] In the fifth aspect of the present disclosure, for example, according to the covering active material of any one of the first to fourth aspects, the mass of the above-mentioned covering layer may also be 4.5% or less of the mass of the above-mentioned covering active material. With such a configuration, the resistance of the battery can be further reduced.

[0037] In the sixth aspect of the present disclosure, for example, according to the covering active material of any one of the first to third aspects, the above-mentioned active material may also be a positive electrode active material. If the technology of the present disclosure is applied to the positive electrode active material, a solid electrolyte with poor oxidation resistance but high ionic conductivity can be used for the positive electrode.

[0038] In the seventh aspect of the present disclosure, for example, according to the covering active material of any one of the first to sixth aspects, the above-mentioned first solid electrolyte may also be represented by the following compositional formula (2). Wherein, x satisfies 0 < x ≤ 1.2, n is the weighted average valence of the elements contained in M, M is a metal or a semi-metal, and X contains fluorine or contains fluorine and chlorine. When the halide solid electrolyte represented by the compositional formula (2) is used in the battery, the charge and discharge efficiency of the battery can be improved.

[0039] Li 6-nx M x X6 Formula (2)

[0040] In the eighth aspect of the present disclosure, for example, in the covering active material according to the seventh aspect, M may be at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr. If such a structure is used, the ion conductivity of the covering layer can be improved, and the resistance of the battery can be effectively reduced.

[0041] In the ninth aspect of the present disclosure, for example, in the coated active material according to the seventh aspect, M may be at least one selected from the group consisting of Al, Ti, and Zr. With such a configuration, the ion conductivity of the coating layer can be improved, and the resistance of the battery can be effectively reduced.

[0042] In the tenth aspect of the present disclosure, for example, in the covered active material according to the seventh aspect, M may be at least one selected from the group consisting of Ti and Al. When M contains Al and / or Ti, the halide solid electrolyte exhibits high ion conductivity.

[0043] In the 11th aspect of the present disclosure, for example, in the covered active material according to the 7th aspect, the ratio of the amount of Li to the total amount of M may be 1.7 to 4.2. With such a configuration, the ion conductivity of the first solid electrolyte can be further improved.

[0044] The electrode material according to the twelfth aspect of the present disclosure includes:

[0045] The covered active material according to any one of the first to eleventh aspects, and

[0046] Second solid electrolyte.

[0047] In a thirteenth aspect of the present disclosure, for example, in the electrode material according to the twelfth aspect, the second solid electrolyte may include a sulfide solid electrolyte.

[0048] A battery according to a fourteenth aspect of the present disclosure includes

[0049] A positive electrode comprising the electrode material according to the twelfth or thirteenth aspect.

[0050] A battery according to a fifteenth aspect of the present disclosure includes:

[0051] A positive electrode comprising the electrode material of the twelfth or thirteenth aspect,

[0052] Negative electrode, and

[0053] An electrolyte layer is disposed between the positive electrode and the negative electrode.

[0054] The electrode material disclosed herein is suitable for suppressing an increase in the resistance of a battery caused by a durability test.

[0055] A method for manufacturing a battery according to a sixteenth aspect of the present disclosure includes:

[0056] Mixing the coated active material of any one of the first to eleventh embodiments with a second solid electrolyte to prepare an electrode material; and

[0057] The electrodes are formed using the above-mentioned electrode materials.

[0058] According to the present disclosure, since the covering layer is not easily peeled off from the active material, the active material is sufficiently protected by the covering layer even in the prepared positive electrode material.

[0059] In the 17th aspect of the present disclosure, for example, in the method for manufacturing a battery according to the 16th aspect, the electrode material may be a slurry containing the covering active material, the second solid electrolyte, and a solvent. According to the present disclosure, the desired effect can be obtained even when the electrode is manufactured by a so-called wet method.

[0060] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.

[0061] (Implementation Method 1)

[0062] Figure 1 1 is a cross-sectional view showing a schematic structure of the coated active material 130 in Embodiment 1. The coated active material 130 includes an active material 110 and a coating layer 111. The active material 110 is in the shape of particles, for example. The coating layer 111 covers at least a portion of the surface of the active material 110.

[0063] The cover layer 111 is a layer containing a first solid electrolyte. The cover layer 111 is provided on the surface of the active material 110. The first solid electrolyte contains a fluoride.

[0064] The first solid electrolyte may be a solid electrolyte containing a halogen. A solid electrolyte containing a halogen is often also referred to as a halide solid electrolyte. The halide solid electrolyte has excellent oxidation resistance. In particular, a halide solid electrolyte containing fluorine (F) has excellent oxidation resistance due to its high electronegativity. Therefore, by covering the active material 110 with the first solid electrolyte, oxidation of other solid electrolytes in contact with the active material 110 can be suppressed. Thus, the increase in resistance of the battery caused by the endurance test can be suppressed.

[0065] The mass of the covering layer 111 that is peeled off from the active material 110 when the covering active material 130 is dispersed in the organic dispersion medium is less than 42% of the total mass of the covering layer 111 .

[0066] If the proportion of the covering layer 111 peeled off from the active material 110 when the covering active material 130 is dispersed in the organic dispersion medium (stripping rate) is less than 42%, the resistance of the battery can be reduced, and the increase in resistance after the endurance test can be suppressed. In the manufacturing process of the battery, there is sometimes a step of dispersing the covering active material, solid electrolyte and auxiliary materials (conductive aids, etc.) in an organic dispersion medium for mixing. In the case of a large peeling rate, the covering layer peels off excessively in this process, resulting in defects in the covering layer. As a result, a sufficient protective effect brought by the covering layer cannot be obtained, resulting in an increase in resistance and resistance after the endurance test. In the case of a peeling rate of less than 42%, since the protective effect brought by the covering layer can be fully obtained, the characteristics of the battery can be improved.

[0067] In this embodiment, the peeling rate of the covering layer 111 from the active material 110 may be 28% or less. In this case, the resistance of the battery can be more effectively reduced. The lower limit of the peeling rate is not particularly limited. The lower limit of the peeling rate may also be 12% or 0%. The peeling rate may also be greater than 12% and less than 28%.

[0068] The peeling rate can be measured by the following method.

[0069] Add the covering active material 130 and the organic dispersion medium to a glass container of 50 ml in size, and disperse the covering active material 130 in the organic dispersion medium to prepare a dispersion. The concentration of the covering active material 130 in the dispersion is, for example, 10% by mass. The temperature of the dispersion is 25°C. The organic dispersion medium may be an organic solvent such as tetralin. It is preferred that the covering material is not easily dissolved in the organic dispersion medium, and the covering active material 130 is easily dispersed in the organic dispersion medium. In other words, it is preferred that the solubility parameter of the first solid electrolyte is moderately different from the solubility parameter of the organic dispersion medium. The dispersion may also contain a dispersant. In the dispersion, the amount of the dispersant is, for example, 10% by mass relative to the amount of the covering active material 130. As a dispersant, an imidazoline-based dispersant may be used. Next, the dispersion is stirred with an ultrasonic homogenizer. The stirring conditions using the ultrasonic homogenizer are, for example, a maximum of 50W, 20kHz, and 1 to 30 minutes. Next, a centrifuge is used to separate the dispersion. The separation treatment is performed under conditions such that only the covering active material 130 settles and only the peeled covering layer 111 is dispersed in the organic dispersion medium.

[0070] The supernatant is quickly collected from the dispersion, transferred to a cell for absorbance measurement, and the absorbance at 400 nm is measured. In the process of dispersing the covering active material 130 in the organic dispersion medium, color may develop. Therefore, the organic dispersion medium without the covering active material 130 is subjected to the same treatment as the dispersion and used as a blank for absorbance measurement.

[0071] On the other hand, a calibration curve showing the relationship between concentration and absorbance is prepared in advance using a dispersion liquid containing only the first solid electrolyte as a covering material.

[0072] The amount of the covering material contained in the supernatant (i.e., the amount of the peeled covering layer 111) is calculated from the absorbance of the supernatant and the standard curve. The ratio of the mass of the peeled covering layer 111 to the total mass of the covering layer 111 contained in the covering active material 130 is calculated as a "peeling rate" from the amount of the covering material contained in the supernatant.

[0073] The total mass of the covering layer 111 can be measured by the following method. That is, the covering active material 130 of known mass is dissolved in acid, and the element group is quantified by ICP (Inductively Coupled Plasma) emission spectrometry. The mass of the covering layer 111 is calculated from the mass of the covering active material 130 and the quantitative value of the element group.

[0074] The absorbance at a wavelength of 400 nm measured for a supernatant obtained by dispersing and precipitating the coating active material 130 in an organic dispersion medium is, for example, less than 0.63.

[0075] The amount of the covering layer 111 that is peeled off when the covering active material 130 is dispersed in the organic dispersion medium is positively correlated with the absorbance of the supernatant. A supernatant with a high absorbance exhibits a high peeling rate, and a supernatant with a low absorbance exhibits a low peeling rate. When the absorbance is lower than the above value, the peeling rate is low, and the characteristics of the battery can be further improved.

[0076] Absorbance not only comprises the influence of absorption produced by material, but also comprises the influence produced by the scattering of particle.According to the relationship between the measuring wavelength and particle diameter, it is affected by geometric scattering, Mie scattering and Rayleigh scattering.Particularly in the region of measuring wavelength>particle diameter, the influence of Rayleigh scattering that becomes significant is caused in proportion to the inverse of the fourth power of wavelength, so the measuring wavelength is shorter, then the apparent absorbance measured by spectrophotometer becomes higher.On the other hand, when the measuring wavelength is too short, the absorption of the glass container used as the measuring pool becomes stronger, so it is difficult to see the influence produced by the sample.Therefore, the measurement under the wavelength of about 400nm is suitable.

[0077] In this embodiment, the absorbance may be less than 0.37. The resistance of the battery can be reduced more effectively. The lower limit of the absorbance is not particularly limited. The lower limit of the absorbance may be 0.16 or zero. The absorbance may be greater than 0.16 and less than 0.37. Zero absorbance means that the absorbance is lower than the detection limit of the spectrophotometer.

[0078] The resistance of the battery increases through a predetermined endurance test. The ratio of the resistance after the endurance test to the resistance before the endurance test is the resistance increase rate (%).

[0079] The increase in resistance caused by the endurance test can be measured by the following method. After the completion of the battery, the charge and discharge process is performed. Thereafter, the battery is charged to a suitable charging voltage of about 2V to 4V. Thereafter, it is discharged at a suitable rate of about 2C to 4C. The resistance (initial resistance) is calculated by dividing the difference between the open circuit voltage just before discharge and the voltage at the moment 10 seconds after the start of discharge by the discharge current value. The calculated resistance is the resistance before the endurance test. Thereafter, the battery is placed in a high temperature tank set at 60°C and charged and discharged 90 times at 1C. Thereafter, the battery is returned to the constant temperature tank at 25°C, and the resistance is measured by the above method. The calculated resistance is the resistance after the endurance test.

[0080] The covering layer 111 may also cover the active material 110 in the same manner.

[0081] The covering layer 111 may cover only a portion of the surface of the active material 110. Since the particles of the active material 110 are in direct contact with each other via the portion not covered by the covering layer 111, the electron conductivity between the particles of the active material 110 is improved. As a result, the battery can operate at a high output power.

[0082] A portion of the covering layer 111 may also have a particle-like structure including a plurality of particles with a diameter of 500 nm or less. Particles with a diameter of 500 nm or less are particles of a halide solid electrolyte serving as a covering material. If the covering layer 111 has a fine particle-like structure, the deformation of the covering layer 111 can be promoted during the manufacture of the electrode plate, thereby being able to form a good interface between the covering active material 130 and other materials. As a result, the resistance of the battery can be further reduced. If the particle is too large, it is necessary to be accompanied by the deformation of the solid electrolyte serving as the covering material, so it is difficult to obtain the above-mentioned effect. The lower limit of the diameter of the particle is not particularly limited, for example, 5 nm.

[0083] The particle-like structure refers to a structure in which a plurality of particles having a diameter of 500 nm or less are connected like beads and are randomly arranged. The diameter of each of the plurality of particles constituting the particle-like structure may be 50 nm or less.

[0084] The particle-like structure including a plurality of particles having a diameter of 500 nm or less can be formed by using particles having a sufficiently small diameter as the covering material and appropriately adjusting the energy given by a processing device when forming the covering layer 111 .

[0085] The covering layer 111 may also have a plurality of pores with a diameter of 50 nm or less. If the covering layer 111 has fine pores, the deformation of the covering layer 111 can be promoted during the manufacture of the electrode plate, so that a good interface can be formed between the covering active material 130 and other materials. As a result, the resistance of the battery can be further reduced. The diameter of each of the plurality of pores may also be 5 nm or less. The lower limit of the diameter of the pore is not particularly limited, for example, 0.5 nm.

[0086] Pores having a diameter of 50 nm or less can be formed by using particles having a sufficiently small diameter as the covering material and appropriately adjusting the energy applied by a processing device when forming the covering layer 111 .

[0087] The “plurality of particles having a diameter of 500 nm or less” and the “plurality of pores having a diameter of 50 nm or less” can be determined by observing the surface of the coating active material 130 at a magnification of, for example, 100,000 times using a scanning electron microscope.

[0088] The mass of the covering layer 111 may be 4.5% or less of the mass of the covering active material 130. If the mass of the covering layer 111 is 4.5% or less of the mass of the covering active material 130, the resistance of the battery can be further reduced. The lower limit of the mass of the covering layer 111 is not particularly limited, and is, for example, 0.1% of the mass of the covering active material 130.

[0089] Next, the active material 110 and the cover layer 111 will be described in detail.

[0090] Active Substance 110

[0091] The active material 110 is, for example, a positive electrode active material. If the technology disclosed in the present invention is applied to the positive electrode active material, a solid electrolyte having poor oxidation resistance but high ion conductivity can be used for the positive electrode. Examples of such solid electrolytes include sulfide solid electrolytes, halide solid electrolytes, and the like.

[0092] The positive electrode active material includes a material having the characteristics of embedding and de-embedding metal ions (for example, lithium ions). As the positive electrode active material, lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal sulfur oxides, transition metal nitrogen oxides, etc. can be used. In particular, as a positive electrode active material, when using lithium-containing transition metal oxides, the manufacturing cost of the battery can be reduced and the average discharge voltage can be increased. As lithium-containing transition metal oxides, Li(NiCoAl)O2, Li(NiCoMn)O2, LiCoO2, etc. can be listed.

[0093] The positive electrode active material may also contain Ni, Co and Al. The positive electrode active material may also be nickel-cobalt-aluminum lithium. For example, the positive electrode active material may also be Li(NiCoAl)O2. If such a structure is used, the energy density and charge and discharge efficiency of the battery can be further improved.

[0094] The active material 110 has a particle shape, for example. The shape of the particle of the active material 110 is not particularly limited. The particle of the active material 110 may be spherical, ellipsoidal, scaly, or fibrous.

[0095] The median particle size of the active material 110 may also be greater than 0.1 μm and less than 100 μm. When the median particle size of the active material 110 is greater than 0.1 μm, a good dispersion state can be formed by covering the active material 130 and other solid electrolytes. As a result, the charge and discharge characteristics of the battery are improved. When the median particle size of the active material 110 is less than 100 μm, the diffusion rate of lithium inside the active material 110 can be fully ensured. Therefore, the battery can operate at high output power.

[0096] In this specification, the “median diameter” refers to the particle diameter at which the cumulative volume in the volume-based particle size distribution is 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measuring device or an image analyzer.

[0097] 《Overlay 111》

[0098] The covering layer 111 contains the first solid electrolyte. The first solid electrolyte has ion conductivity. The ion conductivity is typically lithium ion conductivity. The covering layer 111 may contain the first solid electrolyte as a main component, or may contain only the first solid electrolyte. "Main component" refers to the component that contains the most in mass ratio. "Containing only the first solid electrolyte" means that, except for inevitable impurities, no materials other than the first solid electrolyte are intentionally added. For example, the raw materials of the first solid electrolyte, by-products generated when the first solid electrolyte is made, etc. are included in the inevitable impurities. The ratio of the mass of the inevitable impurities to the overall mass of the first covering layer 111 may also be 5% or less, 3% or less, 1% or less, or 0.5% or less.

[0099] The median particle size of the particles of the covering material used to form the covering layer 111 may also be 500 nm or less. When the median particle size of the particles of the covering material is 500 nm or less, the particles of the covering material can spread evenly on the surface of the active material 110. Furthermore, by applying mechanical energy to the active material 110 and the particles of the covering material, the voids contained therein are crushed, and a thin and uniform covering layer 111 can be formed. The median particle size of the particles of the covering material may also be 100 nm, or may be 60 nm or less. The lower limit of the median particle size of the particles of the covering material is not particularly limited, and is, for example, 1 nm.

[0100] The particles of the covering material used to form the covering layer 111 may be particles of the first solid electrolyte.

[0101] In this specification, the "particle" may be an aggregate of particles or a particle composed of a single particle. That is, the particle may be a secondary particle or a primary particle.

[0102] The specific surface area of ​​the particles of the coating material used to form the coating layer 111 may be 10 m 2 / g or more, can also be 20m 2 / g or more, can also be 40m 2 / g or more. A large specific surface area of ​​the covering material particles is associated with a large volume of the covering material. When the specific surface area of ​​the covering material particles is large, the covering material particles can be uniformly adhered to each other on the surface of the active material 110. As a result, a uniform covering layer 111 can be formed. The upper limit of the specific surface area of ​​the covering material particles is not particularly limited, and is, for example, 100m 2 / g.

[0103] The first solid electrolyte is a solid electrolyte containing fluorine. The first solid electrolyte may also contain Li, M and X. X contains F, and may further contain at least one selected from the group consisting of Cl, Br and I. M may be at least one selected from the group consisting of Ca, Mg, Al, Y, Ti and Zr. Such a material has excellent ion conductivity and oxidation resistance. Therefore, the covering active material 130 having the covering layer 111 of the first solid electrolyte improves the charge and discharge efficiency of the battery and the thermal stability of the battery.

[0104] When X is F, the oxidation resistance of the first solid electrolyte can be further improved.

[0105] The halide solid electrolyte as the first solid electrolyte is represented by, for example, the following composition formula (1). In the composition formula (1), α, β, and δ are each independently a value greater than 0. X contains fluorine.

[0106] Li α Mβ X δ Formula (1)

[0107] Compared with a halide solid electrolyte such as LiI that contains only Li and halogen elements, the halide solid electrolyte represented by Composition Formula (1) has a high ionic conductivity. Therefore, when the halide solid electrolyte having the composition represented by Composition Formula (1) is used in a battery, the charge-discharge efficiency of the battery can be improved.

[0108] The halide solid electrolyte as the first solid electrolyte can also be represented by the following Composition Formula (2). x satisfies 0 < x ≤ 1.2. n is the weighted average valence of the elements contained in M. M is a metal or a semi-metal. X contains fluorine, or contains fluorine and chlorine. When the halide solid electrolyte represented by Composition Formula (2) is used in a battery, the charge-discharge efficiency of the battery can be improved.

[0109] Li 6-nx M x X6 Formula (2)

[0110] M can also be at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr. By introducing polyvalent ions into the crystal structure containing Li and F, the conduction path of lithium ions can be expanded. If such a structure is used, the ionic conductivity of the coating layer 111 can be improved, and the resistance of the battery can be effectively reduced.

[0111] M can also be at least one selected from the group consisting of Al, Ti, and Zr. By adding trivalent or tetravalent polyvalent ions, i.e., the above elements, into the crystal structure containing Li and F, the conduction path of lithium ions can be expanded. If such a structure is used, the ionic conductivity of the coating layer 111 can be improved, and the resistance of the battery can be effectively reduced.

[0112] M can also be at least one selected from the group consisting of Al and Ti. When M contains Al and / or Ti, the halide solid electrolyte exhibits a high ionic conductivity.

[0113] M can also be at least one selected from the group consisting of Al and Y. That is, the halide solid electrolyte can also be at least one selected from the group consisting of Al and Y as the metal element. M can also be Al. When M contains Al and / or Y, the halide solid electrolyte exhibits a high ionic conductivity.

[0114] In order to further improve the ionic conductivity of the first solid electrolyte, in the halide solid electrolyte, the ratio of the amount of substance of Li to the total amount of substance of M can also be 1.7 or more and 4.2 or less. If such a structure is used, the ionic conductivity of the first solid electrolyte can be further improved.

[0115] The halide solid electrolyte may also substantially contain Li, Ti, Al, and X. Here, the statement that "the halide solid electrolyte substantially contains Li, Ti, Al, and X" means that the total molar ratio (i.e., mole fraction) of the amounts of Li, Ti, Al, and X relative to the total amount of the substances of all the elements constituting the halide solid electrolyte is 90% or more. As an example, this molar ratio (i.e., mole fraction) may also be 95% or more. The halide solid electrolyte may also contain only Li, Ti, Al, and X.

[0116] The halide solid electrolyte may also be represented by the following compositional formula (3).

[0117] Li 6-(4-x)b (Ti 1-x M x ) b F6 Formula (3)

[0118] In the compositional formula (3), 0 < x < 1 and 0 < b ≤ 1.5 are satisfied. The halide solid electrolyte having such a composition has a high ionic conductivity.

[0119] In order to further improve the ionic conductivity of the halide solid electrolyte, in the compositional formula (3), M may also be Al.

[0120] In order to further improve the ionic conductivity of the halide solid electrolyte, in the compositional formula (3), 0.1 ≤ x ≤ 0.9 may also be satisfied.

[0121] In the compositional formula (3), 0.1 ≤ x ≤ 0.7 may also be satisfied.

[0122] The upper limit value and the lower limit value of the range of x in the compositional formula (3) may be defined by any combination selected from the values of 0.1, 0.3, 0.4, 0.5, 0.6, 0.67, 0.7, 0.8, and 0.9.

[0123] In order to improve the ionic conductivity of the halide solid electrolyte, in the compositional formula (3), 0.8 ≤ b ≤ 1.2 may also be satisfied.

[0124] The upper limit value and the lower limit value of the range of b in the compositional formula (3) may be defined by any combination selected from the values of 0.8, 0.9, 0.94, 1.0, 1.06, 1.1, and 1.2.

[0125] The halide solid electrolyte may be crystalline or amorphous.

[0126] The shape of the halide solid electrolyte is not particularly limited. The shape of the halide solid electrolyte is, for example, needle-shaped, spherical, or ellipsoidal. The halide solid electrolyte may also be in the form of particles.

[0127] When the shape of the halide solid electrolyte is, for example, a particle shape (for example, a spherical shape), the halide solid electrolyte may have a median particle size of 0.01 μm or more and 100 μm or less.

[0128] The thickness of the covering layer 111 is, for example, not less than 1 nm and not more than 500 nm. If the thickness of the covering layer 111 is appropriately adjusted, the contact between the active material 110 and other solid electrolytes can be sufficiently suppressed. The thickness of the covering layer 111 can be determined by thinning the covering active material 130 using a method such as ion milling and observing the cross section of the covering active material 130 using a transmission electron microscope. The average value of the thickness measured at any multiple positions (for example, 5 points) can be regarded as the thickness of the covering layer 111.

[0129] The halide solid electrolyte may also be a sulfur-free solid electrolyte. In this case, the generation of sulfur-containing gases such as hydrogen sulfide gas from the solid electrolyte can be avoided. A sulfur-free solid electrolyte refers to a solid electrolyte represented by a composition formula that does not contain sulfur elements. Therefore, a solid electrolyte containing a very small amount of sulfur, such as a solid electrolyte having a sulfur content ratio of 0.1% by mass or less, belongs to a sulfur-free solid electrolyte. The halide solid electrolyte may further contain oxygen as an anion other than the halogen element.

[0130] 《Method for producing halide solid electrolyte》

[0131] The halide solid electrolyte can be produced by the following method.

[0132] A plurality of types of raw material powders corresponding to the target composition are prepared and mixed. The raw material powder may be a halide. The halide may also be a compound containing a plurality of elements including a halogen element.

[0133] For example, when the target composition is Li 2.7 Ti 0.3 Al 0.7 In the case of F6, LiF, TiF4 and AlF3 are prepared as raw material powders in a molar ratio of about 2.7:0.3:0.7 and mixed. At this time, by appropriately selecting the type of raw material powder, the element species of "M" and "X" in the composition formula (1) can be determined. By adjusting the type of raw material powder, the mixing ratio of the raw material powder and the synthesis process, the values ​​of "α", "β", "γ" and "δ" in the composition formula (1) can be adjusted. In order to offset the composition changes that may occur in the synthesis process, the raw material powders can also be mixed at a pre-adjusted molar ratio.

[0134] The raw material powders may also be mixed using a mixing device such as a planetary ball mill. The raw material powders are reacted with each other by a mechanochemical grinding method to obtain a reactant. The reactant may also be calcined in a vacuum or in an inert atmosphere. Alternatively, the mixture of the raw material powders may be calcined in a vacuum or in an inert atmosphere to obtain a reactant. The calcination is performed, for example, at a temperature of 100° C. to 400° C. for more than 1 hour. In order to suppress composition changes that may occur during calcination, the raw material powders may also be calcined in a sealed container such as a quartz tube. Through these steps, a halide solid electrolyte is obtained.

[0135] 《Method for manufacturing covering active material 130》

[0136] The coating active material 130 can be manufactured by the following method.

[0137] The powder of the active material 110 and the powder of the first solid electrolyte are mixed at an appropriate ratio to obtain a mixture. The mixture is subjected to a grinding process to impart mechanical energy to the mixture. For the grinding process, a mixing device such as a ball mill can be used. In order to suppress oxidation of the material, the grinding process can also be performed in a dry atmosphere and an inert atmosphere.

[0138] The coating active material 130 can also be manufactured by a dry particle composite method. The treatment by the dry particle composite method includes applying at least one mechanical energy selected from the group consisting of impact, compression, and shear to the active material 110 and the first solid electrolyte. The active material 110 and the first solid electrolyte are mixed at an appropriate ratio.

[0139] The device used in the manufacture of the coating active material 130 is not particularly limited, and may be a device capable of imparting mechanical energy of impact, compression, or shear to the mixture of the active material 110 and the first solid electrolyte. As devices capable of imparting mechanical energy, there can be cited processing devices (particle composite devices) such as a ball mill, "MECHANO FUSION" (manufactured by Hosokawa Micron Group), "NOBILTA" (manufactured by Hosokawa Micron Group), and "BALANCE GRAN" (manufactured by FREUND TURBO).

[0140] "MECHANO FUSION" is a particle compounding device that uses dry mechanical compounding technology that applies strong mechanical energy to multiple different raw material powders. In MECHANO FUSION, mechanical energy such as compression, shearing and friction is applied to the raw material powders placed between the rotating container and the pressure head. This causes the particles to be compounded.

[0141] NOBILTA is a particle compounding device that uses dry mechanical compounding technology developed from particle compounding technology to compound nanoparticles as raw materials. NOBILTA produces composite particles by applying mechanical energy such as impact, compression, and shear to various types of raw material powders.

[0142] In the case of "NOBILTA", a rotor arranged in a horizontal cylindrical mixing container with a predetermined gap between the inner walls of the mixing container is rotated at high speed, and the raw material powder is repeatedly forced to pass through the gap. In this way, impact, compression and shear forces can be applied to the mixture to produce composite particles of the active material 110 and the first solid electrolyte.

[0143] The "BALANCE GRAN" has a chopper that stirs the powder from the outer circumference to the inner circumference in a vortex shape to promote convection, and a stirring blade that rotates in the opposite direction of the chopper. These actions can make the mixture evenly dispersed to produce composite particles.

[0144] In any device, by adjusting the conditions such as the rotation speed, the processing time, the amount of material fed, the particle size of the material, etc., the thickness of the covering layer 111 and the specific surface area of ​​the covering active material 130 can be controlled. The specific surface area decreases as the processing time increases. The specific surface area decreases as the rotation speed of the device increases.

[0145] If the rotation speed of the device is increased, the mechanical energy given to the particles is increased, the adhesion between the active material 110 and the covering layer 111 is improved, and the peeling rate is reduced. Increasing the processing time is also effective in reducing the peeling rate. By adjusting the rotation speed of the device, the processing time, etc. according to the median particle size of the active material 110 and the median particle size of the first solid electrolyte, a covered active material 130 with a desired peeling rate can be obtained. When the amount of the first solid electrolyte as the covering material is increased, there is a tendency for the peeling rate to increase, so in order to reduce the peeling rate, it is preferred to increase the processing time.

[0146] It should be noted that the treatment using the above-mentioned device is not essential. The coated active material 130 can also be manufactured by mixing the active material 110 with the first solid electrolyte using a mortar, a mixer, etc. The first solid electrolyte can also be deposited on the surface of the active material 110 by various methods such as a spraying method, a spray drying coating method, an electrolysis method, an impregnation method, and a mechanical mixing method using a disperser.

[0147] (Variation Example)

[0148] Figure 21 is a cross-sectional view showing a schematic structure of a covering active material 140 in a modified example. The covering active material 140 includes an active material 110 and a covering layer 120. In this modified example, the covering layer 120 includes a first covering layer 111 and a second covering layer 112. The first covering layer 111 is a layer including a first solid electrolyte. The second covering layer 112 is a layer including a base material. The first covering layer 111 is located outside the second covering layer 112. If such a structure is used, the resistance of the battery can be further reduced.

[0149] The first covering layer 111 is the covering layer 111 described in the first embodiment.

[0150] The second covering layer 112 is located between the first covering layer 111 and the active material 110. In this modification, the second covering layer 112 is in direct contact with the active material 110. The second covering layer 112 may include a material with low electron conductivity such as an oxide material or an oxide solid electrolyte as a base material.

[0151] In this modification, the mass of the covering layer 120 peeled off from the active material 110 when the covering active material 140 is dispersed in the organic dispersion medium is less than 42% of the mass of the first covering layer 111. In the case where the second covering layer 112 is formed by a method that is not easy to peel off, such as a liquid phase method, and is composed of a material that is not easy to dissolve, it can be regarded that the first covering layer 111 is selectively peeled off.

[0152] Examples of oxide materials include SiO2, Al2O3, TiO2, B2O3, Nb2O5, WO3, and ZrO2. Examples of oxide solid electrolytes include Li-Nb-O compounds such as LiNbO3, Li-BO compounds such as LiBO2 and Li3BO3, Li-Al-O compounds such as LiAlO2, Li-Si-O compounds such as Li4SiO4, Li2SO4, and Li4Ti5O 12 Li-Ti-O compounds such as Li2ZrO3, Li-Zr-O compounds such as Li2MoO3, Li-VO compounds such as LiV2O5, Li-WO compounds such as Li2WO4, etc. The base material may be one selected from these or a mixture of two or more.

[0153] The base material may also be a solid electrolyte having lithium ion conductivity. The base material is typically an oxide solid electrolyte having lithium ion conductivity. The oxide solid electrolyte has high ion conductivity and excellent high potential stability. By using an oxide solid electrolyte as a base material, the charge and discharge efficiency of the battery can be improved.

[0154] The base material may also be a material containing Nb. The base material typically contains lithium niobate (LiNbO3). If such a structure is used, the charge and discharge efficiency of the battery can be improved. As the base material, i.e., the oxide solid electrolyte, the material described above may also be used.

[0155] In one example, the ion conductivity of the halide solid electrolyte contained in the first covering layer 111 may be higher than the ion conductivity of the base material contained in the second covering layer 112. With such a configuration, oxidation of other solid electrolytes can be further suppressed without sacrificing ion conductivity.

[0156] The thickness of the first covering layer 111 is, for example, greater than 1 nm and less than 500 nm. The thickness of the second covering layer 112 is, for example, greater than 1 nm and less than 500 nm. If the thickness of the first covering layer 111 and the second covering layer 112 is appropriately adjusted, the contact between the active material 110 and other solid electrolytes can be sufficiently suppressed. The thickness of each layer can be determined by the method described above.

[0157] 《Method for manufacturing covering active material 140》

[0158] The coating active material 140 can be manufactured by the following method.

[0159] First, the second covering layer 112 is formed on the surface of the active material 110. The method for forming the second covering layer 112 is not particularly limited. Examples of the method for forming the second covering layer 112 include a liquid phase covering method and a gas phase covering method.

[0160] For example, in the liquid phase coating method, a precursor solution of the base material is applied to the surface of the active material 110. In the case of forming the second covering layer 112 containing LiNbO3, the precursor solution can be a mixed solution (sol solution) of a solvent, a lithium alkoxide, and a niobium alkoxide. As lithium alkoxide, lithium ethoxide can be listed. As niobium alkoxide, niobium ethoxide can be listed. The solvent is, for example, an alcohol such as ethanol. The amount of lithium alkoxide and niobium alkoxide is adjusted according to the target composition of the second covering layer 112. Water can also be added to the precursor solution as needed. The precursor solution can be acidic or alkaline.

[0161] The method of applying the precursor solution to the surface of the active material 110 is not particularly limited. For example, the precursor solution can be applied to the surface of the active material 110 using a rotating flow granulation coating device. If a rotating flow granulation coating device is used, the precursor solution can be blown onto the active material 110 while rotating and flowing the active material 110, and the precursor solution is applied to the surface of the active material 110. Thus, a precursor film is formed on the surface of the active material 110. Thereafter, the active material 110 covered by the precursor film is subjected to a heat treatment. The precursor film is gelled by the heat treatment to form the second covering layer 112.

[0162] As the vapor phase coating method, there can be cited pulsed laser deposition (PLD) method, vacuum evaporation method, sputtering method, thermal chemical vapor deposition (CVD) method, plasma chemical vapor deposition method, etc. For example, in the PLD method, a high-energy pulse laser (for example, KrF excimer laser, wavelength: 248nm) is irradiated to the ion conductive material as a target, so that the sublimated ion conductive material is deposited on the surface of the active material 110. In the case of forming the second coating layer 112 of LiNbO3, LiNbO3 sintered at a high density can be used as a target.

[0163] However, the method for forming the second covering layer 112 is not limited to the above method, and the second covering layer 112 may be formed by various methods such as spraying, spray drying coating, electrolysis, dipping, and mechanical mixing using a disperser.

[0164] After the second covering layer 112 is formed, the first covering layer 111 is formed by the method described in Embodiment 1. Thus, the covering active material 140 is obtained.

[0165] (Implementation Method 2)

[0166] Figure 3 This is a cross-sectional view schematically showing the structure of an electrode material 1000 in the second embodiment.

[0167] The electrode material 1000 includes the covered active material 130 and the second solid electrolyte 100 in the first embodiment. The electrode material 1000 may be a positive electrode material. Instead of the covered active material 130 or together with the covered active material 130, the covered active material 140 of the modified example may also be used. The electrode material 1000 of this embodiment is suitable for reducing the increase in the resistance of the battery caused by the endurance test.

[0168] The active material 110 covering the active material 130 is separated from the second solid electrolyte 100 by the covering layer 111. The active material 110 does not need to be in direct contact with the second solid electrolyte 100. This is because the covering layer 111 has ion conductivity.

[0169] The second solid electrolyte 100 may include at least one selected from the group consisting of a halide solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte.

[0170] Examples of the halide solid electrolyte include the materials described as the first solid electrolyte in Embodiment 1. That is, the composition of the second solid electrolyte 100 may be the same as or different from the composition of the first solid electrolyte.

[0171] The oxide solid electrolyte is a solid electrolyte containing oxygen. The oxide solid electrolyte may further contain anions other than sulfur and halogen elements as anions other than oxygen.

[0172] As oxide solid electrolytes, for example, NASICON solid electrolytes represented by LiTi2(PO4)3 and its element substitution products, (LaLi)TiO3-based perovskite solid electrolytes, and Li 14 ZnGe4O 16 , Li4SiO4, LiGeO4 and their element substitution products represented by LISICON type solid electrolytes, Li7La3Zr2O 12 Garnet-type solid electrolytes represented by Li3PO4 and its element-substituted bodies, glass or glass ceramics obtained by adding Li2SO4, Li2CO3 and other materials to basic materials containing Li-BO compounds such as LiBO2 and Li3BO3, etc.

[0173] As a polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used. The polymer compound may also have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt. Therefore, the ion conductivity can be further improved. As lithium salts, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be listed. One lithium salt selected from them can be used alone, or a mixture of two or more lithium salts selected from them can be used.

[0174] As the complex hydride solid electrolyte, for example, LiBH4-LiI, LiBH4-P2S5, etc. can be used.

[0175] The second solid electrolyte 100 may also contain Li and S. In other words, the second solid electrolyte 100 may also contain a sulfide solid electrolyte. Sulfide solid electrolytes have high ion conductivity and can improve the charge and discharge efficiency of the battery. On the other hand, sulfide solid electrolytes sometimes have poor oxidation resistance. When a sulfide solid electrolyte is included as the second solid electrolyte 100 in a battery, a high effect can be obtained by applying the technology disclosed in the present invention.

[0176] As sulfide solid electrolytes, for example, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 Etc. LiX, Li2O, MO can also be added to them q , Li p MO q etc. Wherein, X in "LiX" is at least one selected from the group consisting of F, Cl, Br and I. "MO q " and "Li p MO q The element M in "MO" is at least one selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe and Zn. q " and "Li p MO q " where p and q are independent natural numbers.

[0177] The second solid electrolyte 100 may include two or more materials selected from the materials listed as solid electrolytes. For example, the second solid electrolyte 100 may include a halide solid electrolyte and a sulfide solid electrolyte.

[0178] The second solid electrolyte 100 may have a lithium ion conductivity higher than that of the first solid electrolyte.

[0179] The second solid electrolyte 100 may contain inevitable impurities such as starting materials, by-products, and decomposition products used in synthesizing the solid electrolyte. This also applies to the first solid electrolyte.

[0180] The shape of the second solid electrolyte 100 is not particularly limited, and may be a needle shape, a sphere shape, an ellipsoidal sphere shape, etc. The shape of the second solid electrolyte 100 may be a particle shape.

[0181] When the second solid electrolyte 100 is in the shape of particles (e.g., spheres), the median particle size may be 100 μm or less. When the median particle size is 100 μm or less, the covering active material 130 and the second solid electrolyte 100 can form a good dispersion state in the electrode material 1000. Therefore, the charge and discharge characteristics of the battery are improved. The median particle size of the second solid electrolyte 100 may also be 10 μm or less.

[0182] The median particle size of the second solid electrolyte 100 may be smaller than the median particle size of the covering active material 130. With such a configuration, the second solid electrolyte 100 and the covering active material 130 can be dispersed in a better state in the electrode material 1000.

[0183] The median particle size of the covering active material 130 may also be greater than 0.1 μm and less than 100 μm. When the median particle size of the covering active material 130 is greater than 0.1 μm, the covering active material 130 and the second solid electrolyte 100 can form a good dispersion state in the electrode material 1000. As a result, the charge and discharge characteristics of the battery are improved. When the median particle size of the covering active material 130 is less than 100 μm, the diffusion rate of lithium inside the covering active material 130 can be fully ensured. Therefore, the battery can operate at high output power.

[0184] The median particle size of the coating active material 130 may be larger than the median particle size of the second solid electrolyte 100. Thus, the coating active material 130 and the second solid electrolyte 100 can be in a well-dispersed state.

[0185] In the electrode material 1000, the second solid electrolyte 100 and the covering active material 130 may also be Figure 3 At this time, the cover layer 111 and the second solid electrolyte 100 are in contact with each other.

[0186] The electrode material 1000 may include a plurality of particles of the second solid electrolyte 100 and a plurality of particles covering the active material 130. That is, the electrode material 1000 may be a mixture of the powder covering the active material 130 and the powder of the second solid electrolyte 100.

[0187] In the electrode material 1000 , the content of the second solid electrolyte 100 and the content of the covering active material 130 may be the same as or different from each other.

[0188] 《Other Materials》

[0189] In the electrode material 1000, for the purpose of improving the adhesion between particles, a binder may also be included. The binder is used to improve the adhesion of the material constituting the electrode. As the binder, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polycarbonate, polyether sulfone, polyether ketone, polyether ether ketone, polyphenylene sulfide, hexafluoropolypropylene, styrene butadiene rubber, carboxymethyl cellulose, ethyl cellulose, etc. can be listed. In addition, copolymers of two or more monomers selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, butadiene, styrene, pentafluoropropylene, fluoromethyl vinyl ether, acrylate, acrylic acid and hexadiene may also be used. One selected from these may be used alone or two or more may be used in combination.

[0190] From the reason of excellent adhesiveness, the binder can also be an elastomer. An elastomer is a polymer with rubber elasticity. The elastomer used as a binder can be a thermoplastic elastomer or a thermosetting elastomer. The binder can also include a thermoplastic elastomer. As a thermoplastic elastomer, styrene-ethylene-butylene-styrene (SEBS), styrene-ethylene-propylene-styrene (SEPS), styrene-ethylene-ethylene-propylene-styrene (SEEPS), butene rubber (BR), isoprene rubber (IR), chloroprene rubber (CR), acrylonitrile-butadiene rubber (NBR), styrene-butylene rubber (SBR), styrene-butadiene-styrene (SBS), styrene-isoprene-styrene (SIS), hydrogenated isoprene rubber (HIR), hydrogenated butyl rubber (HIIR), hydrogenated nitrile rubber (HNBR), hydrogenated styrene-butylene rubber (HSBR), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), etc. can be listed. One selected from them can be used alone, or two or more can be used in combination.

[0191] The electrode material 1000 may also include a conductive additive for the purpose of improving electronic conductivity. As the conductive additive, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black and Ketjen black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, conductive polymer compounds such as polyaniline, polypyrrole, and polythiophene can be used. When a carbon conductive additive is used, low cost can be achieved.

[0192] The above-mentioned conductive auxiliary agent may also be contained in the cover layer 111 .

[0193] 《Method for producing electrode material》

[0194] The electrode material 1000 is obtained by mixing the powder of the coating active material 130 with the powder of the second solid electrolyte 100. There is no particular limitation on the method of mixing the coating active material 130 with the second solid electrolyte 100. The coating active material 130 and the second solid electrolyte 100 may be mixed using a mortar or other apparatus, or may be mixed using a mixing device such as a ball mill.

[0195] (Implementation method 3)

[0196] Embodiment 3 will be described below. The description overlapping with that of Embodiment 1 and Embodiment 2 will be omitted as appropriate.

[0197] Figure 4 2 is a cross-sectional view showing a schematic structure of a battery 2000 in Embodiment 3. The battery 2000 includes a positive electrode 201, a separator layer 202, and a negative electrode 203. The separator layer 202 is disposed between the positive electrode 201 and the negative electrode 203. The positive electrode 201 includes the electrode material 1000 described in Embodiment 2. By using such a structure, it is possible to suppress an increase in the resistance of the battery 2000 caused by a durability test, and provide a battery with excellent durability.

[0198] The thickness of each of the positive electrode 201 and the negative electrode 203 may be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 201 and the negative electrode 203 is 10 μm or more, sufficient battery energy density can be ensured. When the thickness of the positive electrode 201 and the negative electrode 203 is 500 μm or less, the battery 2000 can operate at high output power.

[0199] The diaphragm layer 202 is an electrolyte layer containing an electrolyte material. The diaphragm layer 202 may also contain at least one solid electrolyte selected from the group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte. The details of each solid electrolyte are as described in Embodiments 1 and 2.

[0200] The thickness of the separator layer 202 may be 1 μm or more and 300 μm or less. When the thickness of the separator layer 202 is 1 μm or more, the positive electrode 201 and the negative electrode 203 can be separated more reliably. When the thickness of the separator layer 202 is 300 μm or less, the battery 2000 can operate at a high output power.

[0201] The negative electrode 203 contains a material having a property of inserting and extracting metal ions (for example, lithium ions) as a negative electrode active material.

[0202] As the negative electrode active material, metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be used. The metal material can also be a simple metal. Alternatively, the metal material can also be an alloy. As metal materials, lithium metal, lithium alloys, etc. can be listed. As carbon materials, natural graphite, coke, carbon in graphitization, carbon fiber, spherical carbon, artificial graphite, amorphous carbon, etc. can be listed. From the viewpoint of capacity density, silicon (Si), tin (Sn), silicon compounds, tin compounds, etc. can be suitably used.

[0203] The median diameter of the particles of the negative electrode active material may be 0.1 μm or more and 100 μm or less.

[0204] The negative electrode 203 may include other materials such as a solid electrolyte. As the solid electrolyte, the materials described in Embodiment 1 or 2 can be used.

[0205] How to make a battery

[0206] Figure 5 2 is a flowchart showing a method for manufacturing the battery 2000. In step S1, the positive electrode material is prepared by mixing the covering active material 130 with the second solid electrolyte 100. During the mixing when preparing the positive electrode material, the covering layer 111 may peel off from the covering active material 130. According to the present embodiment, since the covering layer 111 is not easily peeled off from the active material 110, the active material 110 is fully protected by the covering layer 111 in the prepared positive electrode material.

[0207] The positive electrode material may be a slurry including the coating active material 130, the second solid electrolyte 100, and a solvent. According to this embodiment, since the coating layer 111 is not easily peeled off from the active material 110, the desired effect can be obtained even when the electrode is produced by a so-called wet method.

[0208] When the coating active material 130 is a coating negative electrode active material, the coating active material 130 may be used to prepare a negative electrode material.

[0209] Next, in step S2, the positive electrode material is coated on the current collector to form a coating film. The coating film is dried and rolled to obtain a positive electrode. Finally, in step S3, the positive electrode, the electrolyte layer and the negative electrode are combined. Thus, the battery 2000 of this embodiment is obtained.

[0210] Example

[0211] Hereinafter, the present disclosure will be described in detail using examples and comparative examples. It should be noted that the present disclosure is not limited to the following examples.

[0212] <Example 1>

[0213] [Production of halide solid electrolyte]

[0214] In an argon atmosphere with a dew point below -60°C, LiF, TiF4 and AlF3 as raw material powders are weighed in a molar ratio of LiF:TiF4:AlF3=2.7:0.3:0.7. They are placed together with a 0.5 mmφ ball (25 g) in a 45cc pod for a planetary ball mill. γ-Butyrolactone (GBL) as an organic solvent is added dropwise to the pod in such a way that the solid content ratio becomes 50% by mass. The solid content ratio is calculated by {(mass of raw material) / (mass of raw material + mass of solvent)}×100. Using a planetary ball mill, the mixture is ground at 500 rpm for 12 hours. After grinding, the balls are separated to obtain a slurry. Using a mantle-type resistance heater, the slurry is dried at 200°C for 1 hour under a nitrogen flow. The obtained solid is crushed in a mortar to obtain a powder of the halide solid electrolyte of Example 1. The halide solid electrolyte of Example 1 has a 2.7 Ti 0.3 Al 0.7 The composition represented by F6 (hereinafter referred to as "LTAF") is shown in the SEM image. The diameter of each particle of the halide solid electrolyte is within the range of 10 nm to 100 nm.

[0215] [Production of covering active material]

[0216] As a positive electrode active material, powder of Li(NiCoAl)O2 (hereinafter referred to as "NCA") is prepared. Next, a covering layer formed of LTAF is formed on the surface of NCA. The covering layer is formed by a stirring treatment using a large-scale high-speed mixer (BG-25L manufactured by FREUNDTURBO). Specifically, NCA and LTAF are weighed in a mass ratio of NCA:LTAF=97.3:2.7. Using a high-speed mixer, NCA and LTAF are stirred and mixed at 700 rpm for 1 hour. Thereafter, NCA and LTAF are further stirred and mixed at 1300 rpm for 1 hour. Thus, the covered active material of Example 1 is obtained.

[0217] In Table 1, for example, the descriptions "rotation speed 700 rpm, 1300 rpm" and "treatment time 1+1" mean that the treatment was performed at a rotation speed of 700 rpm for 1 hour, and then the treatment was performed at a rotation speed of 1300 rpm for 1 hour.

[0218] [Determination of peeling rate]

[0219] Prepare a tetralin solution containing an imidazoline dispersant at a ratio of 5% by mass. 2g of tetralin solution and 2g of covered active material are placed in a glass container, and 16g of tetralin is added to obtain a mixed solution containing 10% by mass of covered active material. Then, an ultrasonic homogenizer (SMT company system, UH-50) is used to process the mixed solution under the conditions of 20kHz and 10 minutes to obtain a dispersion. Then, the dispersion is placed in a spiral tube for centrifugation, and a centrifuge (DLAB company system, DM0412) is used to separate and process under the conditions of 300rpm and 11 minutes. Afterwards, the supernatant is collected and transferred to a glass cell (optical path length 1cm), and a spectrophotometer (AS ONE company system, ASV11D-H) is used to measure the absorbance at a wavelength of 400nm. As a blank for absorbance measurement, tetralin treated under the conditions of 20kHz and 10 minutes using an ultrasonic homogenizer is used.

[0220] The absorbance of the supernatant obtained by the coating active material of Example 1 was 0.628. The absorbance of the blank was 0.067. The concentration of LTAF in the supernatant was determined from the absorbance obtained by subtracting the absorbance of the blank from the absorbance of the supernatant and the value of the standard curve prepared in advance. The concentration of LTAF in the supernatant was 0.125 mass%. The peeling rate was calculated from the concentration of LTAF in the supernatant (0.125 mass%), the mass of tetralin contained in the dispersion (17.9 g), and the mass of LTAF present in the entire dispersion including the precipitated coating active material (2 g×0.027=0.054 g). As a result, the peeling rate was 42%.

[0221] [Production of sulfide solid electrolyte]

[0222] In an argon glove box with a dew point below -60°C, weigh Li2S and P2S5 as raw material powders in a molar ratio of Li2S:P2S5=75:25. Crush and mix them in a mortar to obtain a mixture. Then, use a planetary ball mill (manufactured by FRITSCH, P-7 type) to grind the mixture for 10 hours at 510 rpm. Thus, a glassy solid electrolyte is obtained. The glassy solid electrolyte is heat treated in an inert atmosphere at 270°C for 2 hours. Thus, a glass-ceramic sulfide solid electrolyte, namely Li2S-P2S5, is obtained.

[0223] [Battery production]

[0224] (Production of positive electrode)

[0225] The covered active material and the sulfide solid electrolyte of Example 1 are weighed in a volume ratio of (covered active material): (sulfide solid electrolyte) = 6:4. They are added to a tetrahydroxynaphthalene solvent together with vapor grown carbon fiber (VGCF) as a conductive aid and styrene-ethylene-butylene-styrene block copolymer (SEBS) as a binder. The resulting mixture is fully dispersed with an ultrasonic homogenizer to prepare a positive electrode paste. The amount of the conductive aid is 3 parts by mass relative to 100 parts by mass of the covered active material. The amount of the binder is 0.4 parts by mass relative to 100 parts by mass of the covered active material. "VGCF" is a registered trademark of Resonac Corporation.

[0226] (Production of negative electrode)

[0227] Lithium titanate and sulfide solid electrolyte as negative electrode active materials are weighed in a volume ratio of (lithium titanate): (sulfide solid electrolyte) = 6.5:3.5. They are added to a tetralin solvent together with vapor-grown carbon fiber (VGCF) as a conductive aid and styrene-ethylene-butylene-styrene block copolymer (SEBS) as a binder. The resulting mixture is fully dispersed with an ultrasonic homogenizer to prepare a negative electrode paste. The amount of the conductive aid is 1 part by mass relative to 100 parts by mass of the negative electrode active material. The amount of the binder is 2 parts by mass relative to 100 parts by mass of the negative electrode active material.

[0228] (Fabrication of all-solid-state batteries)

[0229] The positive electrode paste was applied to an aluminum foil as a positive electrode current collector by a doctor blade method using a coating device to form a coating film, and the coating film was dried on a hot plate at 100° C. for 30 minutes. Thus, a positive electrode having a positive electrode current collector and a positive electrode active material layer was obtained.

[0230] Next, the positive electrode is pressed. Using a die coater, the electrolyte layer forming paste is applied to the surface of the pressed positive electrode active material layer to obtain a stack of the positive electrode and the coating film. The stack is dried on a hot plate at 100°C for 30 minutes. Thereafter, the stack is rolled at a linear pressure of 2 ton / cm. Thus, a positive electrode side stack having a positive electrode collector, a positive electrode active material layer and a solid electrolyte layer is obtained. The electrolyte layer forming paste is prepared by ultrasonically dispersing 0.4 parts by mass of acrylate butadiene rubber as a binder and 100 parts by mass of a sulfide solid electrolyte in a heptane solvent.

[0231] The negative electrode paste was applied on a nickel foil as a negative electrode current collector to form a coating film, and the coating film was dried on a hot plate at 100° C. for 30 minutes. Thus, a negative electrode having a negative electrode current collector and a negative electrode active material layer was obtained.

[0232] Next, the negative electrode is pressed. Using a die coater, the electrolyte layer forming paste is applied to the surface of the pressed negative electrode active material layer to obtain a laminate of the negative electrode and the coating film. The laminate is dried on a hot plate at 100°C for 30 minutes. Thereafter, the laminate is rolled at a linear pressure of 2 ton / cm. Thus, a negative electrode side laminate having a negative electrode collector, a negative electrode active material layer and a solid electrolyte layer is obtained.

[0233] The positive electrode side laminate and the negative electrode side laminate are punched out separately and arranged into a specified shape. The positive electrode side laminate and the negative electrode side laminate are overlapped in such a way that the solid electrolyte layers are in contact with each other. Afterwards, the positive electrode side laminate and the negative electrode side laminate are rolled at 130°C and a linear pressure of 2 ton / cm. Thus, a power generation element having a positive electrode, a solid electrolyte layer and a negative electrode in sequence is obtained. The positive terminal and the negative terminal are installed on the obtained power generation element, sealed in a container made of a laminated film, and constrained at a pressure of 5 MPa, thereby obtaining the all-solid-state battery of Example 1.

[0234] [DC resistance measurement]

[0235] The DC resistance of the all-solid-state battery was measured by the following method: constant current charging was performed at a current of 1C, and after the battery voltage reached 2.95V, constant voltage charging was performed at 2.95V, and charging was terminated when the charging current reached 0.01C. Then, constant current discharge was performed at a current of 1C, and discharge was terminated when the battery voltage dropped to 1.5V.

[0236] In order to measure the DC resistance, the all-solid battery was charged again to 2.2V at a current of C / 3, and then discharged at a current of 4C. The DC resistance (initial resistance) was calculated by dividing the difference between the open circuit voltage just before the 4C discharge and the voltage at the moment 10 seconds after the discharge start by the current value of 4C. The results are shown in Table 1.

[0237] [Durability test]

[0238] The all-solid-state battery was placed in a thermostatic chamber at 60°C and charged and discharged repeatedly for 90 cycles at a current of 1C. Afterwards, the all-solid-state battery was returned to a thermostatic chamber at 25°C, and the DC resistance was measured by the method described above to calculate the DC resistance after the endurance test. The ratio of the DC resistance after the endurance test to the DC resistance before the endurance test was calculated as the resistance increase factor.

[0239] <Example 2>

[0240] The covered active material of Example 2 was prepared by the same method as Example 1, except that the treatment using the high-speed mixer was performed at 700 rpm for 1 hour, 1300 rpm for 1 hour, and 1900 rpm for 2 hours. Thereafter, the peeling rate of the covered active material of Example 2 was measured by the same method as Example 1. Using the covered active material of Example 2, an all-solid-state battery was prepared by the same method as Example 1, and the DC resistance and the increase rate of resistance were measured.

[0241] <Example 3>

[0242] The covered active material of Example 3 was prepared by the same method as Example 1 except that the treatment using the high-speed mixer was performed at 1950 rpm for 3 hours. Thereafter, the peeling rate of the covered active material of Example 3 was measured by the same method as Example 1. Using the covered active material of Example 3, an all-solid-state battery was prepared by the same method as Example 1, and the DC resistance and the increase rate of resistance were measured.

[0243] [SEM observation]

[0244] The surface covered with the active material of Example 3 was observed using a scanning electron microscope (manufactured by Hitachi High-Tech, Regulus 8220, 0.5 kV, 100,000 times). The results are shown in FIG. Figure 8 middle. Figure 8 This is a SEM image of the surface covered with active material in Example 3. Figure 8 In the SEM image, the large bumps and depressions reflect the bumps and depressions of the NCA itself. LTAF particles are attached to the surface of the NCA. The concave parts on the surface of the NCA are filled with a covering layer of LTAF. The covering layer covering the active material has a particle-like structure P1 containing multiple particles with a diameter of less than 500nm, and the fine particles contained in the particle-like structure P1 are particles of LTAF as a covering material. In addition, a plurality of pores P2 with a diameter of less than 50nm are formed in the covering layer. The thin LTAF film exists in a manner that fills the bumps and depressions on the surface of the NCA, and pores P2 are formed in the film. It is speculated that these structures promote the deformation of the covering layer during the manufacture of the electrode plate, and contribute to the formation of a good interface between the covering active material and other materials.

[0245] <Example 4>

[0246] The covered active material of Example 4 was prepared by the same method as in Example 1 except that the treatment using the high-speed mixer was performed at 1950 rpm for 4 hours. Thereafter, the peeling rate of the covered active material of Example 4 was measured by the same method as in Example 1. Using the covered active material of Example 4, an all-solid-state battery was prepared by the same method as in Example 1, and the DC resistance and the increase rate of resistance were measured.

[0247] <Comparative Example 1>

[0248] The covered active material of Comparative Example 1 was prepared by the same method as in Example 1 except that the treatment using the high-speed mixer was performed at 700 rpm for 1 hour. Thereafter, the peeling rate of the covered active material of Comparative Example 1 was measured by the same method as in Example 1. Using the covered active material of Comparative Example 1, an all-solid-state battery was prepared by the same method as in Example 1, and the DC resistance and the resistance increase factor were measured.

[0249] The absorbance measurement results, the peeling rate calculation results, the DC resistance measurement results, and the resistance increase factor calculation results are shown in Table 1. In Table 1, the DC resistance is a relative value when the DC resistance of Comparative Example 1 is regarded as "100". Similarly, the resistance increase factor is a relative value when the resistance increase factor of Comparative Example 1 is regarded as "100". The absorbance of Example 4 is 0.000, which is the same as the measured value of the blank.

[0250] Figure 6 Graph showing the relationship between DC resistance and peeling rate. The horizontal axis shows the peeling rate in Table 1. The vertical axis shows the DC resistance in Table 1. Figure 7 1 is a graph showing the relationship between the increase factor of the resistance and the peeling rate. The horizontal axis shows the peeling rate in Table 1. The vertical axis shows the increase factor of the resistance in Table 1.

[0251] Table 1

[0252]

[0253] ※ The DC resistance and resistance increase times are relative values ​​when the values ​​of Comparative Example 1 are regarded as "100"

[0254] <Inspection>

[0255] like Figure 6 As shown in , the DC resistance decreases as the peeling rate decreases. When the peeling rate is around 25%, the DC resistance shows a minimum value, and if the peeling rate further decreases, the DC resistance turns to increase. Figure 7 As shown in , the resistance increase rate improves with decreasing peeling rate.

[0256] A high peeling rate means that the cover layer is easily peeled off from the active material during the production of the electrode plate. When the peeling rate is high as in Comparative Example 1, the DC resistance and the increase factor of the resistance are high. It is believed that the reason is that the cover layer peels off from the active material and cannot fully protect the active material.

[0257] A low peeling rate indicates that the covering layer is not easy to peel off from the active material during the manufacture of the electrode plate. In Examples 1 to 4, the covering state of the active material brought by the covering layer can be maintained, and the direct contact between the sulfide solid electrolyte and the active material is suppressed. As a result, it is believed that the increase in DC resistance and resistance after the endurance test is suppressed.

[0258] It should be noted that an excessively low peeling rate indicates that the covering layer is attached to the active material more than necessary. In this case, the ion conduction distance increases due to the excessive thickness of the covering layer, and it is considered that as a result, the DC resistance increases.

[0259] Industrial Applicability

[0260] The technology disclosed in the present invention is useful for, for example, all-solid-state lithium secondary batteries.

Claims

1. A coated active material, which comprises an active material and a coating layer, wherein the coating layer contains a first solid electrolyte and covers at least a part of the surface of the active material, the first solid electrolyte contains a fluoride, when the coated active material is dispersed in an organic dispersion medium, the mass of the coating layer peeled off from the active material is less than 42% of the total mass of the coating layer.

2. The covered active material according to claim 1, wherein The absorbance at a wavelength of 400 nm obtained by measuring the supernatant obtained by dispersing and precipitating the coated active material in the organic dispersion medium is less than 0.

56.

3. The covered active material according to claim 1, wherein: The coating layer has a particle-like structure including a plurality of particles with a diameter of 500 nm or less.

4. The covered active material according to claim 1, wherein The coating layer has a plurality of pores with a diameter of 50 nm or less.

5. The covered active material according to claim 1, wherein The mass of the coating layer is 4.5% or less of the mass of the coated active material.

6. The covered active material according to claim 1, wherein: The active material is a positive electrode active material.

7. The covered active material according to claim 1, wherein: The first solid electrolyte is represented by the following compositional formula (2), wherein x satisfies 0 < x ≤ 1.2, n is the weighted average valence of the elements contained in M, M is a metal or a semi-metal, and X contains fluorine or contains fluorine and chlorine, Li 6-nx M x Model X6(2).

8. The covered active material according to claim 7, wherein: M is at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr.

9. The coated active material according to claim 7, wherein: M is at least one selected from the group consisting of Al, Ti, and Zr.

10. The coated active material according to claim 7, wherein: M is at least one selected from the group consisting of Ti and Al.

11. The coated active material according to claim 7, wherein: The ratio of the amount of substance of Li to the total amount of substance of M is 1.7 or more and 4.2 or less.

12. An electrode material, which comprises: the coated active material according to claim 1, and a second solid electrolyte.

13. The electrode material according to claim 12, wherein The second solid electrolyte contains a sulfide solid electrolyte.

14. A battery, which comprises a positive electrode containing the electrode material according to claim 12.

15. A battery, which comprises: a positive electrode containing the electrode material according to claim 12, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode.

16. A method for manufacturing a battery, which includes: mixing the coated active material according to claim 1 with a second solid electrolyte to prepare an electrode material, and forming an electrode using the electrode material.

17. The method for manufacturing a battery according to claim 16, wherein: The electrode material is a slurry containing the coated active material, the second solid electrolyte, and a solvent.